Answer:
x =
![(s-y)/(3-r)](https://img.qammunity.org/2022/formulas/mathematics/high-school/oatbe4bniw5uvzs3movjuen1utmf8vh3au.png)
Explanation:
3x + y = xr + s
Subtract y from both sides:
3x + y = xr + s
3x + y - y = xr + s - y
3x = xr + s - y
Next, subtract xr from both sides:
3x - xr = xr + s - y - xr
3x - xr = s - y
Then, factor out x from the left-hand side:
x( 3 - r ) = s - y
Finally, divide both sides by (3 - r) to solve for x:
x( 3 - r ) = s - y
![(x (3 - r))/(3 - r) = (s - y)/(3 - r)](https://img.qammunity.org/2022/formulas/mathematics/high-school/vzojfhfhqsnhhrpzqkfaq2ngkag3taov94.png)
x =
![(s-y)/(3-r)](https://img.qammunity.org/2022/formulas/mathematics/high-school/oatbe4bniw5uvzs3movjuen1utmf8vh3au.png)